THU0585 ONLINE EDUCATION YIELDS SIGNIFICANT GAINS IN RHEUMATOLOGISTS' KNOWLEDGE OF THE JAK INHIBITORS MODE OF ACTION AND CLINICAL TRIAL DATA. (13th June 2020) - Stan, A.; Calle, M.; Scot-Smith, C.; Van Vollenhoven, R.
Abstract : Background: Physicians face challenges staying up-to-date with the latest research and accessing the ever-growing field of knowledge is time-consuming. Online education can make these clinician's tasks more efficient and less time-consuming. Objectives: This study assessed whether the online CME accredited round-table-discussion with title " Meet the JAKs: Understanding the Role of Janus Kinase Inhibition in RA " improves physicians' understanding mechanism of action (MOA) of current and emerging Janus kinase (JAK) inhibitors and rationale for their development in rheumatoid arthritis (RA). Methods: Rheumatologists participated in an online CME activity (https://www.medscape.org/viewarticle/913625 ) consisting of a 30-minute video discussion between 2 experts with accompanying slides. Educational effect was assessed using a 4-question repeated pairs, pre-/post-assessment. A chi-square test was used to determine if a statistically significant improvement ( P <.05 significance level) existed in the number of correct responses from the pretest and posttest scores. Cramer's V was used to estimate the level of impact of the education. The CME activity launched on June 4, 2019, and the data were collected through September 3, 2019. Results: A total of 107 rheumatologists completed the pre- and post activity assessments. Overall the activity had a signficiant impact ( P <.001) on rheumatologists' knowledge of JAK inhibitors and related clinical trial data with a Cramer's V value of 0.319 indicating an extensive educational impact. The average percentage of correct responses rose from 47% pre-activity to 78% post-activity. The repeated pairs analysis (each individual learner tracked pre- and post-education) showed that 34% of learners improved their knowledge and 44% reinforced their knowledge. The change in percentage of correct responses from pre- to post-assessment achieved statistical significance for all 3 questions presented: (1) understanding the MOA of JAK inhibitors vs biologics (64% at baseline rising to 82% post acivity; P <0.01), (2) understanding the specificity of different JAK inhibitors (49% at baseline rising to 85% post acivity; P <.001), (3) knowledge of clinical trial outcomes with JAK inhibitors (29% at baseline rising to 67% post acivity; P <.001) and (4) 60% of rheumatologists gained confidence in their ability to describe the MOA of current and emerging JAK inhibitors. Conclusion: This online CME activity significantly improved rheumatologists' understanding of JAK inhibitors mode of action. However, there is clearly room for further improving physicians' knowledge of clinical trial outcomes with these agents, since one third of rheumatologists provided incorrect answers to question 3 post-activity) and this topic can be further addressed in future education. Acknowledgments: This CME-certified activity was supported by an independent educational grant from AbbVie. Disclosure of Interests: Adriana Stan Grant/research support from: The CME-certified activity was supported by an independent educational grant from Sandoz., Marinella Calle Grant/research support from: This CME-certified activity was supported by an independent educational grant from Novartis AG, Camille Scot-Smith Grant/research support from: This CME-certified activity was supported by an independent educational grant from AbbVie, Ronald van Vollenhoven Grant/research support from: BMS, GSK, Lilly, UCB, Pfizer, Roche, Consultant of: AbbVie, AstraZeneca, Biogen, Biotest, Celgene, Gilead, Janssen, Pfizer, Servier, UCB, Speakers bureau: AbbVie, Pfizer, UCB